The development of a standardised diet history tool to support the diagnosis of food allergy. Issue 1 (19th February 2015) - Skypala, Isabel J; Venter, Carina; Meyer, Rosan; de Jong, Nicolette W; Fox, Adam T; Groetch, Marion; Oude Elberink, J N; Sprikkelman, Aline; Diamandi, Louiza; Vlieg‐Boerstra, Berber J; ,
Abstract: The disparity between reported and diagnosed food allergy makes robust diagnosis imperative. The allergy‐focussed history is an important starting point, but published literature on its efficacy is sparse. Using a structured approach to connect symptoms, suspected foods and dietary intake, a multi‐disciplinary task force of the European Academy of Allergy and Clinical Immunology developed paediatric and adult diet history tools. Both tools are divided into stages using traffic light labelling (red, amber and green). The red stage requires the practitioner to gather relevant information on symptoms, atopic history, food triggers, foods eaten and nutritional issues. The amber stage facilitates interpretation of the responses to the red‐stage questions, thus enabling the practitioner to prepare to move forward. The final green stage provides a summary template and test algorithm to support continuation down the diagnostic pathway. These tools will provide a standardised, practical approach to support food allergy diagnosis, ensuring that all relevant information is captured and interpreted in a robust manner. Future work is required to validate their use in diverse age groups, disease entities and in different countries, in order to account for differences in health care systems, food availability and dietary norms.